Sensillar Dynamics in Thrips-Flower Interactions of Arid and Semi-arid Tree Species - Murugesan, S; Kumar, Shivesh; Sundararaj, R (Annals of Arid Zone, 2016)
Extensive survey was carried out in order to study the thrips-nower interactions of some introduced/native tree species of arid and semi-arid areas. The behavioural response involved in feeding are modified according to the sensillary structures and functions of the antennae and mouth parts. Though no work in this direction has been undertaken forestry thrips. an analysis of diverse type of olfactory sensilla on the antenna of different species would appear important and measures have to be adopted to protect the forest tree species from flower thrips.